HUBUNGAN DUKUNGAN KELUARGA DENGAN KECEMASAN PASIEN GAGAL GINJAL KRONIK DI RUANG HEMODIALISA RUMAH SAKIT ROYAL PRIMA MEDAN - Anggeria, Elis (Jurnal Keperawatan Priority, 2019)
Patients with chronic renal failure who undergo hemodialysis often experience a decrease in physical activity and this decrease affects the anxiety condition. The family support may decrease anxiety in patients undergoing hemodialysis therapy. The purpose of this study to analyze the relationship between family supports with anxiety patients with chronic renal failure in the hemodialysis chamber Royal Prima Hospital Medan in 2017. The design of this study is analytic with correlative. The population was of 56 people and the technique of sampling using correlation description technique then the sample of 56 people. Data collection was using questionnaire sheet. The results of the study 51 respondents 91.1% known to get good family support and as many as 39 respondents 69.6% known to have moderate anxiety. The result of spearman rho test show significant level p = 0,05 obtained p value = 0,779 so p> 0,05 then Ho accepted. The conclusion of this research is no relationship of family support with anxiety of chronic renal failure patient in hemodialysis chamber of Royal Prima Hospital Medan. Researchers are further advised to examine the effect of family support in decreasing anxiety levels of patients undergoing hemodialysis in the hemodialysis.